2017
DOI: 10.17219/acem/61987
|View full text |Cite
|
Sign up to set email alerts
|

History of discovery of polycystic ovary syndrome

Abstract: Stein and Leventhal are regarded to have been the first investigators of polycystic ovary syndrome (PCOS); however, in 1721 Vallisneri, an Italian scientist, described a married, infertile woman with shiny ovaries with a white surface, and the size of pigeon eggs. It was not until the early 1990s at a National Institute of Health (NIH) sponsored conference on PCOS that formal diagnostic criteria were proposed and afterwards largely utilized. Many scientists tried to explain the pathophysiology of PCOS and many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 23 publications
(26 reference statements)
0
16
0
7
Order By: Relevance
“…Polycystic ovary syndrome (PCOS) is a common endocrine disorder in women, affecting approximately 5%-10% women of reproductive age (Beydoun et al, 2009). It is characterized by oligomenorrhea and ovulatory dysfunction, clinical or biochemical hyperandrogenism, and polycystic ovary morphology (Teede et al, 2011;Szydlarska et al, 2017). This disorder is often associated with insulin resistance, hypertension, infertility, obesity, and weight-related disorders (Bentley-Lewis et al, 2011;Stepto et al, 2013;Joham et al, 2015;Balen et al, 2016;Bergh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is a common endocrine disorder in women, affecting approximately 5%-10% women of reproductive age (Beydoun et al, 2009). It is characterized by oligomenorrhea and ovulatory dysfunction, clinical or biochemical hyperandrogenism, and polycystic ovary morphology (Teede et al, 2011;Szydlarska et al, 2017). This disorder is often associated with insulin resistance, hypertension, infertility, obesity, and weight-related disorders (Bentley-Lewis et al, 2011;Stepto et al, 2013;Joham et al, 2015;Balen et al, 2016;Bergh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Now there is strong evidence that cardiovascular disease risk factors and disturbances in carbohydrate metabolism are all increased in patients with PCOS compared with the healthy population. The other very important point that has been made is that the basis of treatment is the modification of lifestyle [14] . In a study conducted by Hugar AL [15] regarding the prevalence and clinical manifestations of PCOS, the authors observed that between 5-10% women of reproductive age suffer from PCOS and most common symptoms of PCOS are obesity, acne, amenorrhea, irregular menstrual cycles, Hirsutism, insulin resistance and high cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…En 1721, el científico italiano Vallisneri describió el caso de una mujer casada, infertil, con ovarios brillantes de superficie blanca, del tamaño de huevos de paloma. Otro informe, según Szydlarska (4) es de 1844, cuando Chereau y Rokitansky describieron lesiones esclerofibrosas de un carácter degenerativo en ovarios con folículos hidrópicos. Bulius y Kretschmar describieron hipertecosis por primera vez.…”
Section: Historia De La Endocrinologíaunclassified
“…Como sabemos, las células de la teca se encargan de la producción de andrógenos ováricos y también retoman andrógenos más débiles provenientes de las suprarrenales como la DHEA-S y los convierten en testosterona, las de la granulosa producen estrógenos (por acción de una aromatasa sobre los andrógenos), cosa que también ocurre en el tejido graso para formar estrona. Continúa la autora polaca Szydlarska (4) : En 1879 Lawson Tait presentó la necesidad de http://revistaendocrino.org/ ooforectomía bilateral para el tratamiento de la degeneración quística ovárica sintomática, sugiriéndose después la resección parcial de los ovarios. En 1902 von Kahlden publicó una revisión de la patología e implicaciones clínicas de dichos ovarios.…”
Section: Historia De La Endocrinologíaunclassified